A quality of life study on children with atopic dermatitis: an assessment of the impact and effects of severity of atopic dermatitis on affected patients and thier families - Govender, Kiasha (My University, 2017)
Atopic dermatitis is a chronic, debilitating disease affecting children worldwide, with increasing prevalence. It has been shown to be a significant problem leading to a diminished quality of life, for both the affected patient and their families. Quality of life in Atopic Dermatitis is poorly researched. Few studies have been conducted worldwide. There have been no published reports on QOL in children with atopic dermatitis from South Africa. This study aims to assess and evaluate the clinical severity of atopic dermatitis in children less than 6 years of age and the Quality of Life in these patients and their families, as well as to determine the socioeconomic and clinical factors that predict quality of life in children with atopic dermatitis at Chris Hani Baragwanath Academic Hospital (the busiest paediatric dermatology clinic in South Africa). The Childhood Atopic Dermatitis Impact Scale (CADIS) and Patient Oriented Eczema Measure (POEM) were given to the primary caregiver and the SCORAD was performed on each child during a single visit to the Paediatric Dermatology Outpatient Clinic at Chris Hani Baragwanath Academic Hospital (CHBAH) in Soweto. The study parameters show that atopic dermatitis has a negative impact on the quality of life of affected children and their families, in keeping with similar studies internationally. The severity of atopic dermatitis was a significant predictor of quality of life. The poor socioeconomic status was evident in the demographic details of the sample. A significant predictor of quality of life was the age of the affected child, with a higher impairment in child and family QOL experienced for children less than 1 year of age. The QOL measure showed a higher correlation to the caregiver assessment of severity than to the physician’s assessment, suggesting that patient derived outcome measures should be of most importance in adequately assessing disease severity. There is a need for further research of children in South Africa with atopic dermatitis. This is essential to identify effective interventions to improve disease severity and Q.O.L in these children. This would result in the development of children into healthy adults capable of effective family, community and social interaction.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Dermatology. Johannesburg 2017
Keywords: Quality of Life Dermatitis